2014
DOI: 10.1021/es502099g
|View full text |Cite
|
Sign up to set email alerts
|

The Chromium Detoxification Pathway in the Multimetal Accumulator Silene vulgaris

Abstract: Phytomanagement could be a viable alternative in areas polluted with wastes from chromium-using industries. This study investigated the ability of Silene vulgaris to take up Cr(III) and Cr(VI) with special attention on the mechanism used by this species to tolerate high doses of Cr(VI). Plants were grown semihydroponically with different concentrations of either Cr(III) or Cr(VI). A combination of synchrotron X-ray spectroscopic techniques, scanning electron and light microscopy and infrared spectroscopy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…Regardless of whether it is present as Cr(III) or Cr(VI) in the soil solution, Cr accumulates almost exclusively as Cr(III) within plant roots, this being demonstrated in both soil‐based systems and nutrient solutions, including for Indian mustard [ Brassica juncea (L.) Czern.] (Bluskov et al, 2005), subterranean clover ( Trifolium brachycalycinum L.) (Howe et al, 2003), Silene vulgaris (Moench) Garcke (Pradas del Real et al, 2014), Prosopis L. spp. (Aldrich et al, 2003), Convolvulus arvensis L. (Montes‐Holguin et al, 2006), and Parkinsonia aculeate (Zhao et al, 2009).…”
Section: Determining the Distribution And Speciation Of Trace Metal(lmentioning
confidence: 99%
See 4 more Smart Citations
“…Regardless of whether it is present as Cr(III) or Cr(VI) in the soil solution, Cr accumulates almost exclusively as Cr(III) within plant roots, this being demonstrated in both soil‐based systems and nutrient solutions, including for Indian mustard [ Brassica juncea (L.) Czern.] (Bluskov et al, 2005), subterranean clover ( Trifolium brachycalycinum L.) (Howe et al, 2003), Silene vulgaris (Moench) Garcke (Pradas del Real et al, 2014), Prosopis L. spp. (Aldrich et al, 2003), Convolvulus arvensis L. (Montes‐Holguin et al, 2006), and Parkinsonia aculeate (Zhao et al, 2009).…”
Section: Determining the Distribution And Speciation Of Trace Metal(lmentioning
confidence: 99%
“…The first study to demonstrate this conversion to Cr(III) using bulk XANES was Zayed et al (1998a), who examined a wide range of vegetable crops. Whether the transformation from Cr(VI) to Cr(III) occurs within the rhizosphere or rapidly on uptake by the root is unclear (Pradas del Real et al, 2014), but regardless, concentrations of Cr(VI) in root tissues are often sufficiently low that they are not easily detectable using synchrotron‐based approaches. Within root tissues, this Cr(III) is often complexed with simple organic acids (Howe et al, 2003; Bluskov et al, 2005; Zhao et al, 2009), although Pradas del Real et al (2014) found that Cr accumulated in the apoplast of the root apical tissues.…”
Section: Determining the Distribution And Speciation Of Trace Metal(lmentioning
confidence: 99%
See 3 more Smart Citations